Penerapan Lean Six Sigma untuk Meningkatkan Kualitas Layanan dalam Proses Rantai Pasoka di PT.X - Mochamad Bagus Setiyawan; Seto Wahyu Prasetyo; Siti Mujanah; Achmad Yanu Alif Fianto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The manufacturing sector in Indonesia, particularly in the automotive cable and component industry, is facing significant challenges, as reflected in the declining Purchasing Manager’s Index (PMI), indicating a contraction in production activities. To remain competitive, managing production process quality becomes essential, especially in improving supply chain performance. This study examines the application of Six Sigma in the copper busbar production process at PT. X, focusing on reducing supply chain costs through enhanced process quality management and waste reduction. Using the DMAIC approach (Define, Measure, Analyze, Improve, Control), this research analyzes copper busbar production data, including defect rates and associated costs before and after improvements. The results show that Six Sigma implementation successfully reduced defect rates, particularly scratch defects, from 7.32% to 0.01%. Additionally, this improvement contributed to a reduction in supply chain costs, with total savings amounting to IDR 3,421,168,671, covering reductions in manufacturing, administration, warehouse, and capital costs. These findings demonstrate that Six Sigma can significantly enhance efficiency and effectiveness in copper busbar production, while positively impacting overall supply chain costs. The study also recommends further research to more thoroughly explore distribution and installation costs in the supply chain context.